20th century deposition from Baltic Sea ship traffic - Claremar, Björn; Rutgersson, Anna (Uppsala University, 2018)
Historical atmospheric depositions of sulphate, nitrate, and ammonium from land and shipping in the BalticSea.

When using this dataset, please also cite: Omstedt, A., Edman, M., Claremar, B., and Rutgersson, A.: Modelling the contributions to marine acidification from deposited SOx , NOx , and NHx in The Baltic Sea: past and present situations, Cont. Shelf Res., 111, 234–249, https://doi.org/10.1016/j.csr.2015.08.024, 2015.

Data för historiska atmosfäriska avsättningar av sulfat, nitrat och ammonium från land och frakt i Östersjön.

När du använder det här datasetet kan du också citera: Omstedt, A., Edman, M., Claremar, B., and Rutgersson, A.: Modelling the contributions to marine acidification from deposited SOx , NOx , and NHx in The Baltic Sea: past and present situations, Cont. Shelf Res., 111, 234–249, https://doi.org/10.1016/j.csr.2015.08.024, 2015.
20th century deposition from Baltic Sea ship traffic
Keywords: ATMOSPHERIC NITRIC ACID; NITROGEN OXIDES; SULFUR DIOXIDE; SULFATE; NITRIC ACID; PH; TRANSPORTATION; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi